2019
DOI: 10.1371/journal.pgen.1008193
|View full text |Cite
|
Sign up to set email alerts
|

A Flp-SUMO hybrid recombinase reveals multi-layered copy number control of a selfish DNA element through post-translational modification

Abstract: Mechanisms for highly efficient chromosome-associated equal segregation, and for maintenance of steady state copy number, are at the heart of the evolutionary success of the 2-micron plasmid as a stable multi-copy extra-chromosomal selfish DNA element present in the yeast nucleus. The Flp site-specific recombination system housed by the plasmid, which is central to plasmid copy number maintenance, is regulated at multiple levels. Transcription of the FLP gene is fine-tuned by the repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 99 publications
(149 reference statements)
2
12
0
Order By: Relevance
“…The increase in Flp1-induced nicks concomitant with a lack of regulatory control over HR, would lead to the aberrant processing of the replicated plasmids into monomers in daughter cells, thus HMW aggregate formation. This is consistent with that slx5 and slx8 still produces toxic 2-µm plasmid forms even when Flp-SUMO is expressed, despite being attenuated in strand cleavage (Ma et al, 2019). The reason would be deficient regulation on HR proteins.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The increase in Flp1-induced nicks concomitant with a lack of regulatory control over HR, would lead to the aberrant processing of the replicated plasmids into monomers in daughter cells, thus HMW aggregate formation. This is consistent with that slx5 and slx8 still produces toxic 2-µm plasmid forms even when Flp-SUMO is expressed, despite being attenuated in strand cleavage (Ma et al, 2019). The reason would be deficient regulation on HR proteins.…”
Section: Discussionsupporting
confidence: 87%
“…The reduced turnover of Flp1 when irc20 is mutated is similar to that observed in siz1 siz2 , slx5 and slx8 which affect the SUMOylation and/or the subsequent ubiquitin dependent degradation of Flp1 (Ma et al, 2019). The resulting increase in copy number and formation of HMW aggregates is, however, different in case of irc20 mutants.…”
Section: Discussionsupporting
confidence: 62%
“…The identification of MMS21 led us to initially suspect that this locus might represent another connection between the SUMO-ligation machinery and 2μ plasmid stability ( Dobson et al, 2005 ; Zhao et al, 2004 ; Pinder et al, 2013 ; Ma et al, 2019 ). However, the location of the Thr69Ile missense change at the binding interface between Mms21 and Smc5 ( Figure 5—figure supplement 3 ) suggested a mechanism that relies on the Smc5/6 complex rather than the catalytic RING domain.…”
Section: Discussionmentioning
confidence: 99%
“…2plasmid stability is frequently compromised in heterospecific (other species) hosts, suggesting it is actively adapting to maintain stability within its native host species 37 . Our discovery of a natural host variant of S. The identification of MMS21 led us to initially suspect that this locus might represent another connection between the SUMO-ligation machinery and 2plasmid stability 34,35,55,92 . However, the location of the Thr69Ile missense change at the binding interface between Mms21 and Smc5 (Figure supplement 3) suggested a mechanism that relies on the Smc5/6 complex rather than the catalytic RING domain.…”
Section: Mms21 Natural Variation Within S Cerevisiae and Between Senmentioning
confidence: 99%
“…Most studies of 2µ plasmid plasmids (including this one) have focused on the A-type variant that is most commonly found in laboratory strains. However, new sequencing studies have revealed that S. cerevisiae strains harbor a diverse set of 2µ plasmid The identification of MMS21 led us to initially suspect that this locus might represent another connection between the SUMO-ligation machinery and 2-micron plasmid stability 34,35,55,91 . However, the location of the Thr69Ile missense change at the binding interface between Mms21 and Smc5 (Supplementary Figure S9) suggested an alternate mechanism that relies on the Smc5/6 complex.…”
Section: Discussionmentioning
confidence: 99%